Coworking - Rus, Andrej (Teorija in praksa, 2015)
The number of coworking spaces and the number of people who choose to work in them has exploded over the past few years, with numbers expected to double every year. What is fuelling this growth and where is the demand for coworking coming from? We tried to address this question by looking at the specific needs of the rising creative class, identifying their urgent need for uninhibited sharing of information, knowledge, ideas and also material resources. We argue that coworking spaces are favoured by the creative class, because they offer a community of work which facilitates the culture of sharing. To illustrate what it takes to establish such a community of work, we present a case study of the Creative Centre Poligon which suggests that community building is a multi-step process that needs careful management and plenty of time. We conclude that policy makers should not focus on building coworking spaces in order to combat youth unemployment but should rather support existing initiatives that have been built or are in the process of building up vibrant communities of work.
Keywords: Cooperation; coworking; Organizacija dela; Organization of labour; sodelo; Sodelovanje; soustvarjanje